2022
DOI: 10.1111/jgs.17950
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department‐to‐community care transition barriers: A qualitative study of older adults

Abstract: Background Over one‐half of older adults are discharged to the community after emergency department (ED) visits, and studies have shown there is increased risk of adverse health outcomes in the immediate post‐discharge period. Understanding the experiences of older adults during ED‐to‐community care transitions has the potential to improve geriatric emergency clinical care and inform intervention development. We therefore sought to assess barriers experienced by older adults during ED‐to‐community care transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 38 publications
1
44
0
Order By: Relevance
“…Our study findings indicate that providing written discharge instructions is likely insufficient to enhance education for Veterans about their VA ED follow-up care. This finding echoes that of Gettel et al, 12 who interviewed older non-Veterans about their discharge experiences and found that lengthy ED discharge instructions were not helpful. Improving the quality of written instructions, through individualization, 34 illustrations, 35,36 and simplifications appropriate for patients at all levels of health literacy, 37,38 may make them more useful.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our study findings indicate that providing written discharge instructions is likely insufficient to enhance education for Veterans about their VA ED follow-up care. This finding echoes that of Gettel et al, 12 who interviewed older non-Veterans about their discharge experiences and found that lengthy ED discharge instructions were not helpful. Improving the quality of written instructions, through individualization, 34 illustrations, 35,36 and simplifications appropriate for patients at all levels of health literacy, 37,38 may make them more useful.…”
Section: Discussionsupporting
confidence: 82%
“…However, inadequate follow‐up care after ED visits and deficits in communication between ED and follow‐up care providers are common and worthy of attention 7 . Although improving post‐ED care has been prioritized by several commissions, accreditors, and funders, 2,8–11 there remains a relative paucity of evidence‐based practices for reducing care fragmentation across the ED treat‐and‐release transition; further study and intervention development are needed 2,12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we chose to focus on care partners of PLWCI, as the unique experiences of those with intact cognition would likely identify separate barriers and themes during the ED discharge care transition. 21 Described in greater detail below, PLWCI were identified through the electronic medical record as well as through in‐ED cognitive testing to additionally capture those with MCI. Historically, the presence of dementia or MCI has been underdocumented in the electronic medical record and underrecognized in the ED.…”
Section: Methodsmentioning
confidence: 99%
“…10 As an example in ED-based CTI research, one mixed-methods study found no change in 60-day acute care use in the intervention group; however, patient, provider, and coach interviews used to explore the reasons for return ED visits after the intervention revealed that structural features of the health care system (outside of the CTI itself) were a large driver of patient revisits. 2 Other previous work on CTIs in the ED setting has focused more generally on discharges and care transitions outside of any specific intervention, examining the perspectives of older adult patients, 11 patients and caregivers with an ED visit for a fall, 12 and ED providers. 13 There is a great need for more insight into the patient experience of a CTI itself.…”
Section: Introductionmentioning
confidence: 99%